Thermosensitive star polymers — synthesis and properties - Dworak, A.; Trzebicka, B.; Kowalczuk, A.; Utrata-Wesołek, A.; Wałach, W.; Libera, M.; Kronek, J. (Polimery, 2012)
Two kinds of termosensitive star polymers have been synthesized: stars with arms of poly(2-ethyl-2-oxazoline) and stars with arms of poly(tert-butyl glycidyl ether)-b-(polyglycidol). Under applied polymerization methods (living anionic and living cationic polymerization) the topology of the obtained polymers (number and length of star arms) have been controlled and low molar mass dispersities achieved. By the proper choice of structural parameters (nature of the core and the arms and, in the case of copolymer stars, the composition of the arms) polymers ranging from water soluble to termosensitive polymers of controlled cloud point temperature in water have been obtained. The star structure has been correlated with their thermosensitivity.